The 5th Annual Cinema Revival: A Festival of Film Restoration in Columbus, Ohio. Issue 2 (1st September 2019) - Jacobs, Matthew; DeSola, Zachary
The Wexner Center for the Arts showcased thirteen films over six days during its 5th annual Cinema Revival: A Festival of Film Restoration. These films ranged over a variety of genres and featured world-renowned directors and actors. The films featured over the weekend have origins that stretch the globe. From Argentina to Italy, the festival programming allowed viewers to get a glimpse into the history of world cinema, while the speakers introduced the films and shared not only their knowledge but also the detailed steps required for each films restoration. Although some films received more attendance than others, the festival was successful in its goal of sharing classic cinema with a modern audience and providing an even mix of technical discussion, background information, and entertainment.